(3QSGdI aj GdOYGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SGdJ HdZc Gddg GdSYGOI GdbUhi Cf ChVM dc hMbjbI GdOYGA hJCKjQgG ai GdfahS hGdGHOGf EYde Cf dgPg GdeSFdI ebOeGJ hgj eYQaI GdehLhOGJ s
(3BNQgG (B:s
(3hGdELJfGH Yf GdThGZd hGdYhGFb hGdJUQa HGdacQ Edi bOS GdLHQhJ Efg deG jQjO NjQ aYGd hGddg CYde HGdUhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(5/3063) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs